Re-situating the Sa’ban Ethnography: a reflection on the notion of representation. - Egay, Kelvin (Universiti Kebangsaan Malaysia, 2009)
This paper discusses the notion of representation in Sarawak ethnography. It suggests that critical reviews on Sarawak’s ethnographies are lacking despite the numerous ethnographic accounts of its peoples since the Brooke era. Also, the production of text through ethnographic research can alter the realities of the communities in the present time. The scarce ethnographic accounts of the Sa’ban have depended primarily on the writings by the anthropologists, missionaries and few government officers who have been in contact with the Sa’ban since the 1950s. However, these ethnographic texts have not been critically reviewed. As a result of the methodological distortion in the production of the text, the Sa’ban representation is marginalised from the wider Malaysian society. Borrowing Mookerjea’s (2003) term in describing the Subject as a ‘conceptual personae’, the Sa’ban becomes marginalised from participating in their own socio-political realities. To illustrate this, this paper examines the Sa’ban ethnography based on two brief but important accounts of the Sa’ban by Ose Murang, which were published in the Sarawak Museum Journal and Borneo Research Council special bulletin. This article challenges the ethnographers, social anthropologists, historians, sociologists and social scientists as a whole to critically review the existing writings on cultures in Sarawak. It argues that if this issue is not addressed in Sarawak ethnography, there is a danger that ethnographic texts in the absence of critical review may influence the social and political realities of the subject. If anything, this article hopes to offer the ethnographer an alternative but critical strategy of writing and reading ethnography.